SISTEM KELAS TUNTAS BERKELANJUTAN (SKTB) IN GOWA REGENCY; DETERMINATION SOLUTIONS ON STUDENTS DROPOUT - Burhan, Burhan; Widodo, Suparno Eko; Sutjipto, Sutjipto (International Conference on Cultural Studies, 2019)
Education is an effort to improve the quality of human resources. Therefore, improving the quality of education must receive more serious attention. For this reason, it is only natural that policy issues related to improving the quality of education in Indonesia are the main concern of the central and regional governments. Even the foundation of the contextual implementation of education is based on the commitment and policies of the local government and the active role of the community. This research aims to find out how the Sistem Kelas Tuntas Berkelanjutan (SKTB) in Gowa Regency is a solution for completing school dropouts. This study uses evaluation with a qualitative approach with research instruments using interviews, observation and documentation. Sources of data in this study include the Head of Education, Principals, Teachers and Communities. Data analysis using analytical techniques from Miles and Huberman. The results of the study show that with the existence of a policy of a sustainable class system can increase the interest of interest to go to school and continue to a higher level and students can develop competencies according to their interests and abilities. This shows that this policy is certainly one of the alternative solutions in cutting off the school dropout chain because this policy does not recognize the class living system, but instead replaces it with remedial aspects that need to be improved. This is very helpful for parents in motivating children who are educated